THE COMPLEXITY OF ALZHEIEMER’S DISEASE - NEW FRONTIERS - Stefanova, Elka (Medicinski podmladak, 2024)
Alzheimer's disease (AD) represents one of the most significant challenges in the field of neurodegenerative diseases of our time, with its increasing prevalence and lack of curative treatments, which highlights the urgent need for innovative therapeutic strategies.AD is a progressive disorder characterized by cognitive decline, impaired daily functioning and loss of independence. AD pathology is characterized by the accumulation of amyloid beta plaques and neurofibrillary tau protein tangles in the brain, accompanied by neuroinflammation and synaptic dysfunction. Genetic factors, such as mutations in the genes for APP, PSEN1 and PSEN2, directly cause familial forms, while the APOE e4 allele only contributes to an increased risk for the development of AD.Advances in the identification and validation of reliable biomarkers from cerebrospinal fluid (CSF) and blood hold great promise for improving early diagnosis, monitoring disease progression, and assessing response to treatment not only in research but also in clinical practice in an effort to alleviate the burden of this devastating disease. Blood biomarkers in particular promise to significantly improve diagnostic accuracy and effectively simplify referral processes, and early diagnosis as well as timely access to treatment. Ongoing efforts shaping the integration of blood biomarkers in various clinical settings are paving the way toward precision medicine in AB. Research efforts are focused on the development of disease-modifying therapies that target the underlying pathological mechanisms of AD.The current transformative period of knowledge about AD represents an important moment and promises significant changes in clinical conditions in the light of innovative immunotherapy that changes the course of the disease. Given the potential barriers that may impede access to AD therapy, and the need to expand treatment options beyond specialized centers, blood and CSF biomarkers provide an attractive option for screening and early detection of AD and monitoring treatment efficacy. This approach could be a testable scenario for how future clinical implementation could be designed, and how treatments proven to be successful in treating AD could be applied in daily clinical practice with widespread use of biomarkers.
Keywords: subjective cognitive decline; mild cognitive imapirment; diagnostic criteria; genetics; fluid biomarkers; immunotherapy